SCIENTIFÍC OVERVIEW OF EUCALYPTUS CULTIVATION IN TOCANTINS: A BIBILIOMETRIC ANALYSIS OF SCIENTIFÍC PRODUCTION (REMUNOM, 2026)
This study aimed to analyze the scientific landscape of research on the cultivation and management of Eucalyptus from 1986 to 2026. The findings indicate that Eucalyptus production plays a strategic role in Brazilian forestry, particularly in tropical regions and within the Cerrado biome, where forest plantations contribute substantially to the supply of timber, biomass, and raw materials for the pulp and energy sectors. However, environmental constraints, including highly weathered soils, climatic variability, and recurrent periods of water deficit, may limit plantation growth and productivity, thereby requiring management practices and genetic improvement strategies capable of enhancing both productivity and the sustainability of these forest systems. A quantitative, descriptive, and exploratory bibliometric review was conducted in accordance with PRISMA guidelines. Data were collected from the Scopus database using descriptors related to Eucalyptus cultivation and silviculture within the TITLE-ABS-KEY field. The initial search retrieved 37.767 records, which were subsequently reduced to 1.006 documents after thematic and geographical refinement. Following the removal of duplicates and the application of eligibility criteria based on the screening of titles, abstracts, and full texts, the final dataset comprised 28 scientific articles. The results reveal a steady increase in scientific output over recent decades, with a marked concentration of publications in journals specializing in forest sciences, particularly Forest Ecology and Management. The findings also point to the strong leadership of Brazilian institutions and the consolidation of international research networks, accentuate the global relevance of studies focused on productivity, management, and sustainability in Eucalyptus plantations.